Toxic volatiles as tools for the selective isolation of soil fungi and modulating their metabolism / Zuhra Bashir Khalifa Trabalsiy - Bashir Khalifa Trabalsiy, Zuhra (Institute of Graduate Studies, UiTM, 2016)
The fungal kingdom forms an important source for a broad range of secondary metabolites with widely different chemical structures, as well as diverse biological activities. In the present work, the main objective was to isolate fungi from local soil samples and identify bioactive metabolites that they could produce. To this end, soil samples were collected from a biological forest reserve, at UiTM’s Puncak Alam Campus, Malaysia. The isolation from soils can proceed through many different techniques. Here, a new chemotechnique based on the use of five volatile compounds (dimethylsulphoxide, naphthalene, cineole, petroleum and formaldehyde) was used. As a result, a total of 82 fungi were isolated from soil samples taken at three different depths. The pure cultures were inoculated and fermented in the presence or in the absence of volatile compounds. A total of 100 crude extracts were analysed by HPLC and evaluated for antimicrobial activity against pathogenic microorganisms using the MTT assay. Twenty out of 100 crude extracts showed significant antibacterial activity against Escherichia coli, 17 extracts were active against Enterococcus faecium, 15 against Pseudomonas aeruginosa and 25 against Staphylococcus aureus. Twenty six crude extracts showed antifungal activity against Candida albicans. From the analysis of the above data, 8 out of the 82 fungal isolates were selected for further study. These include Aspergillus nomius, A. terreus, Byssochlamys nivea, Talaromyces aculeatus, P. commune, Pseudallescheria minutispora, Trichoderma citrinoviride, and T. virens, which were fully identified by morphological and genetic techniques. Their metabolites were purified by semi-preparative HPLC and identified by spectroscopic (MS, NMR, UV/Vis) and X-ray diffraction techniques…